Audit risk assessment in small enterprises gaps and challenges - Tina Indriana; Agus Widarsono (Indonesia Auditing Research Journal, 2026)
The study is intended to explore the implementation of audit risk assessment in small enterprises and to identify the gaps and practical challenges that auditors face. A qualitative descriptive approach was adopted with data collection through interviews, observations and document analysis of public accountants. The findings suggest that although the risk assessment procedures are conceptually in line with auditing standards, their implementation in practice is still sub-optimal. There are material deficiencies in knowledge of the entity, assessment of internal controls, setting of materiality and retention of adequate audit documentation. Small enterprises are more likely to have higher inherent and control risks due to weak internal control systems, limited financial records and low accounting competence. All these factors increase the probability of material misstatements. Auditors are also faced with unreliable data and unstructured business processes, which hinder the effective implementation of risk-based auditing. Under such circumstances the auditor may have to rely more on professional judgment which may impact on the consistency and reliability of the audit. The research stresses the importance of more adaptive and context-sensitive audit approaches that are more relevant to the specific features of small enterprises and pragmatic insights to improve the quality of the audit and the effectiveness of the risk assessment practices.